Modern Management in the Global Mining Industry - Adams, Robin G. (Emerald Publishing Limited, 2019)
This book brings together perspectives from economics, specifically minerals economics, to the management of global mining companies. It covers volatile price forecasting, cost analysis, investment decisions, and the social, environmental, and developmental impacts of mining.